5 Animal performance in grass monoculture or silvopasture systems using tree legumes. (28th November 2020) - da Silva, Izabela Aline Gomes; Dubeux, Jose Carlos Batista; de Mello, Alexandre C Leão; da Cunha, Márcio Vieira; dos Santos, Mércia Ferreira; Apolinário, Valéria Oliveira; da Silva, Gleise Medeiros; de Freitas, Erinaldo Viana; DiLorenzo, Nicolas
Abstract: Silvopasture systems (SPS) area management option to enhance delivery of ecosystem services and diversification of income. This study evaluated productive responses of signalgrass (Urochloadecumbens Stapf.) in monoculture or in SPS in the sub-humid tropical region of Brazil during six months of the rainy season. The experimental design was randomized complete block with three replications. Treatments were signalgrass + Mimosa caesalpiniifolia Benth. (SPS-Mimosa); signalgrass + Gliricidia sepium (Jacq.) (SPS-Gliricidia); and signalgrass monoculture. Cattle were managed under continuous stocking with variable stocking rate. Response variables included herbage mass (HM), herbage accumulation (HA), stocking rate (SR), average daily gain (ADG), and gain per area (GPA). Herbage mass (HM) was greater (P < 0.0001) on signal grass monoculture (2045 kg DM/ha) than in SPS (1370 kg DM/ha, average for both SPS). Herbage accumulation rate was similar for signalgrass in monoculture and SPS-Gliricidia (avg. 61 kg DM ha -1 d -1 ), and both were greater than SPS-Mimosa (37 kg DM ha -1 d -1 ). Average daily gain was greater(P < 0.0001) for SPS-Gliricidia (1.1 kg head -1 d -1 ), followed by signalgrass in monoculture (0.9 kg head -1 d -1 ), and SPS-Mimosa (0.3 kg head -1 d -1 ). Stocking rate ranged from 0.6 animal units (1AU = 450-kg animal) per ha in April to 2.2 AUha -1 in June. Stocking rate and animal performance per area were similar for signalgrass in monoculture and SPS-Gliricidia, and both greater than SPS-Mimosa. Gliricidia enhanced animal performance and provided ecosystem services. Mimosa, however, reduced animal performance likely due to the competition with signalgrass. Mimosa trees, however, are an important source of income (timber used for fence posts) and that might overcome the losses in animal performance.